2018
DOI: 10.1029/2018gl078430
|View full text |Cite
|
Sign up to set email alerts
|

The Inequality of Climate Change From 1.5 to 2°C of Global Warming

Abstract: The Paris Agreement aims to keep global warming well below 2°C above preindustrial levels with a preferred ambitious 1.5°C target. Developing countries, especially small island nations, pressed for the 1.5°C target to be adopted, but who will suffer the largest changes in climate if we miss this target? Here we show that exceeding the 1.5°C global warming target would lead to the poorest experiencing the greatest local climate changes. Under these circumstances greater support for climate adaptation to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(122 citation statements)
references
References 25 publications
4
114
0
4
Order By: Relevance
“…Such regional preference of hot spots in the tropics seems not quite surprising, considering the well-known smaller natural variability and less variable climates there (Stocker, 2014). Hence, previous univariate-based analyses similarly located climate change hot spots to hot extremes in the tropics as well, though they did not document influences of 0.5°C on emergence timings of hot extremes (King & Harrington, 2018;Mahlstein et al, 2011;Schleussner et al, 2016). However, using univariate-defined hot days (daily maxima ≥ 90th percentile), both the increase in frequency at individual warming levels and added frequency due to the 0.5°C rise would be underestimated by several folds there (Figure 5a).…”
Section: Comparisons With Univariate-based Estimatesmentioning
confidence: 77%
“…Such regional preference of hot spots in the tropics seems not quite surprising, considering the well-known smaller natural variability and less variable climates there (Stocker, 2014). Hence, previous univariate-based analyses similarly located climate change hot spots to hot extremes in the tropics as well, though they did not document influences of 0.5°C on emergence timings of hot extremes (King & Harrington, 2018;Mahlstein et al, 2011;Schleussner et al, 2016). However, using univariate-defined hot days (daily maxima ≥ 90th percentile), both the increase in frequency at individual warming levels and added frequency due to the 0.5°C rise would be underestimated by several folds there (Figure 5a).…”
Section: Comparisons With Univariate-based Estimatesmentioning
confidence: 77%
“…Keeping global warming to 1.5°C, rather than 2.0°C, limits these uneven distributions. King and Harrington (2018) indicated that the ratios of annual mean temperature differences (2.0°C minus 1.5°C) and the internal variability are larger in lower-income countries. Russo et al (2019) suggested that heatwave exposure and an illustrative heatwave risk index (the product of the probability of heatwave occurrence, exposure and a proxy for vulnerability) at the 1.5°C warming level for the population living in low development countries is expected to be greater than those at the 2°C warming level for the population living in very high development countries.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The projected surface temperature increase in the 21st century over Africa is estimated to be faster than the global average increase, specifically in more arid regions (Engelbrecht et al, 2015;Niang et al, 2014). The continent is not only warming more rapidly than most regions elsewhere, but the smaller interannual temperature variability which African regions experience, especially in the tropics, lead to higher signal-to-noise ratios, hence resulting in such areas becoming even more vulnerable to climate change (Harrington et al, 2016;King & Harrington, 2018). A 3-5°C temperature increase is projected over the tropical regions of Africa by the end of the 21st century relative to current climate (Engelbrecht et al, 2015) under the low mitigation scenario (A2: Intergovernmental Panel on Climate Change, IPCC, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, West Africa on average is projected to experience a 3 to 6°C summer temperature increase between 1981-2000and 2031-2050(Diallo et al, 2012 under the A1B emission scenario (IPCC, 2000). Consequently, heat-related extreme events are also estimated to increase more rapidly in most parts of Africa, which also suffer from low adaptive capacities (IPCC, 2012; King & Harrington, 2018;Niang et al, 2014). ©2019.…”
Section: Introductionmentioning
confidence: 99%